RASISME DALAM KEPEMIMPINAN DI INDONESIA (Perspektif Hadis) - Istiqomah, Nor (Jurnal Ilmiah Ilmu Ushuluddin, 2018)
Cases of racism have occurred in the early days of the emergence of Islam, which later became the political legitimacy in which in the leadership space in the Arabian Peninsula the tribe of Quraish is a tribe that dominates. This is reinforced by the argument of hadith which became the basis of that legitimacy. Nonetheless, in fact, there are many other propositions that seem quite contrary to the proposition, such as the Qurâan and other hadith. Therefore, the hadith about political racism which in this case about the domination of tribal leadership of Quraish becomes important to be reinterpreted by using hermeneutic point of view and contextualization of hadith. With this view, the election of a leader is not based on a particular tribe, although assessing of the leadership qualities of the future leader as well as his responsibility in carrying out the mandate of the leader. In the context of Indonesian, the dominance of a tribe in political space is controlled by the political interest of various circles, such as political elites and radical groups. The view that political domination held by a particular group is only used as a âscapegoatâ to overthrow the political opponents.